El arranque tritonal en el español amazónico de Iquitos - Vásquez Aguilar, Alonso (2019)
This article presents a particular phenomenon of intonation in the Amazonian Spanish of Iquitos, a city located in the Peruvian Amazonia: the so-called tritonal start-up. This phenomenon consists of a complex tonal accent L+H*+L produced during the first tonic syllable of the intonational phrase. For this purpose, samples of the oral production by speakers of this dialectal variety were recorded and then analyzed using the autosegmental and metrical model (Pierrehumbert 1980) and the Sp_ToBI prosodic annotation system (Beckman et al. 2002). The data present and distinguish wide-focus and narrow-focus constructions. The analysis of the data confirms a tendency towards a tritonal start-up that is independent of the focus.